Clínica quirúrgica de los cuerpos extraños en el abdomen: Oblito quirúrgico abdominal. - NUÑEZ HUERTA, Edgar (Revista Médica Herediana, 2013)
Philosophic medical and legal principles are stated introducing the name oblito, explaining its linguistic root.the definition of foreing body accidentally forgotten during an operation and with no therapeutic value, is proposed. The characteristics of the foreing body left in the abdomen during surgery from the nosographic and nosologic point of view, give this process an individuality, that allows to speak about its clinics. The symptomatology is clear and connected to the clinical forms analyzed.diagnosis is reached specially by radiology. In orden to complete the oblito’s pathological similitude with other abdominal processes, it is necessary to point out that it has a regulated prophilaxis, in nearly every surgical center.